2016
DOI: 10.1186/s12884-016-0997-6
|View full text |Cite
|
Sign up to set email alerts
|

A pre-post study of a multi-country scale up of resuscitation training of facility birth attendants: does Helping Babies Breathe training save lives?

Abstract: BackgroundWhether facility-based implementation of Helping Babies Breathe (HBB) reduces neonatal mortality at a population level in low and middle income countries (LMIC) has not been studied. Therefore, we evaluated HBB implementation in this context where our study team has ongoing prospective outcome data on all pregnancies regardless of place of delivery.MethodsWe compared outcomes of birth cohorts in three sites in India and Kenya pre-post implementation of a facility-based intervention, using a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 14 publications
2
69
0
Order By: Relevance
“…A previous study in the same setting reported only partial improvements in quality and time of execution of midwife performances after participation in an adapted NRP course [18]. These findings were consistent with previous studies adopting different training programmes [6,23]. Ersdal et al [6] showed that 1-day HBB training courses in Tanzania improved performance in simulated scenarios several months after training, but it did not translate into improved delivery room management.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A previous study in the same setting reported only partial improvements in quality and time of execution of midwife performances after participation in an adapted NRP course [18]. These findings were consistent with previous studies adopting different training programmes [6,23]. Ersdal et al [6] showed that 1-day HBB training courses in Tanzania improved performance in simulated scenarios several months after training, but it did not translate into improved delivery room management.…”
Section: Discussionsupporting
confidence: 80%
“…Ersdal et al [6] showed that 1-day HBB training courses in Tanzania improved performance in simulated scenarios several months after training, but it did not translate into improved delivery room management. Bellad et al [23] showed that HBB training was not associated with consistent improvements in mortality rates among all neonates ≥1,500 g in India and Kenya. The implementation of quality improvement interventions and low-dose/ high-frequency training including in situ simulation may facilitate the transfer of new knowledge/skills into clinical practice, thereby reducing perinatal mortality in Tanzania, Nepal and Sudan [7,15,24].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the largest, most methodologically sound studies evaluating the HBB’s impact demonstrate a decrease in either newborn mortality rate (NMR) or fresh stillbirth rate (FSR) from before to after training mostly at large hospitals where data collection occurred before HBB was provided [1115]. As discussed above, since the relative burden of newborn mortality is likely more significant in rural regions not regularly attended by physicians, birth attendants working in these areas are in greater need of resuscitation skills and therefore are a more ideal target population for HBB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to outcomes relating to skills retention, previous research has also demonstrated an association between HBB training and either decreased newborn mortality rate or decreased fresh stillbirth rate (suggesting many apneic newborns were improperly labeled as stillborn) [1115]. However, although some of these studies included low-volume rural clinics, the majority of births evaluated in these studies occurred in hospitals or larger clinics staffed full-time by physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Significant reductions occurred in one geographic cluster of facilities with high mortality both for stillbirths (25.7 to 16.4/1000 births; estimated mean difference 11.27, 95% CI 0.95, 21.59, p = 0.03) and perinatal deaths (38.5 to 28.2/1000 births; estimated mean difference 11.71, 95% CI 0.39, 23.03, p = 0.04). In facilities with lower baseline rates of stillbirth (7.7-11.6/1000 births) and perinatal death (10.0-25.5/1000 births), there was no significant reduction post scale-up of resuscitation (4). In a post hoc analysis stratified by birthweight, the rates for LBW (<2500 g) fresh stillbirths, early neonatal deaths and perinatal deaths did decrease at one of these sites.…”
mentioning
confidence: 83%